The Effect of Local Government Size, Regional Complexity, Capital Expenditure, PAD, and Economic Growth on Weaknesses of Local Government Internal Control - Resmiyati ANSAR; Rizky Wahyu Utami OHORELA (International Journal of Environmental, Sustainability, and Social Science, 2022)
One form of reform is the granting of authority to local governments to regulate their own regions. The granting of this authority is regulated in the regional autonomy law package, which started from Law no. 32 of 2004. The spirit of Law 32 was then followed up with the issuance of various regulations that others serve as a legal umbrella for local governments in carrying out their autonomous functions. This study aims to analyze the effect of Local Government Size, Regional Complexity, Capital Expenditure, PAD, and Economic Growth on the Weakness of Local Government Internal Control (Empirical Study in Regencies/Cities in North Maluku Province 2015-2019). The method used in this research is quantitative research. The sample in this study is the Regency/City of North Maluku Province (Ternate City, City of Tidore Islands, West Halmahera, East Halmahera, South Halmahera, North Halmahera, Mid Halmahera, Morotai Island, Sula Islands, Taliabu). The data is processed using SPSS. The results show that the size of the local government, regional complexity, capital expenditure, PAD and economic growth affect the weakness of internal control. Suggestions that can be put forward by researchers based on research results are to conduct research by expanding the object of research to other areas in Indonesia.